(untitled) - David R Kinsley (Englewood Cliffs, New Jersey, 1993)
The book deals histirically and anatically with many facets of Hindu culture: philosophy, art, mythology, ritual, and social strusture. Detailed descriptions of specific rituals and extended portraits of important Hindu thinkers and saints are included
Keywords: hinduism